Increased inflammation and intracellular calcium caused by ultrafine carbon black is independent of transition metals or other soluble components. Issue 10 (1st October 2000) - Brown, D M; Stone, V; Findlay, P; MacNee, W; Donaldson, K
Abstract : OBJECTIVES: Particulate air pollution has been shown to cause adverse health effects, and the ultrafine particle component has been implicated. The aim of the present study was to investigate whether an ultrafine particle exerted its effects through transition metals or other soluble factors released from the surface of the particles. METHODS: Both in vitro and in vivo models were used to test the imflammogenicity of carbon black (CB) and ultrafine carbon black (UfCB) and the role of transition metals was investigated by treating the particles with desferrioxamine mesylate (desferal), a transition metal chelator. Rats were instilled with particles and the cell population assessed by bronchoalveolar lavage (BAL). Calcium homeostasis in macrophages was assessed with a fluorimetric technique. RESULTS: UfCB was inflammogenic compared with CB when instilled into Wistar rat lungs, an effect which could not be ameliorated by desferal treatment of the particles. Particle leachates produced no significant inflammation in vivo. In vitro experiments showed that the cytosolic calcium ion concentration in Mono Mac 6 cells was increased significantly after UfCB treatment and treatment of particles with desferal did not alter these effects. Particle leachates had no effect on cytosolic calcium ion concentration. Iron was not detected in leachates of the particles with the desferal assay, however, ng/mg of particles were detectable in citrate leachates with inductively coupled plasma-mass spectrometry (ICP-MS). CONCLUSIONS: The increased inflammogenicity of UfCB compared with CB cannot be explained by soluble transition metals released from or by accumulation of iron at the particle surface. Differences may be accounted for by increased surface area or particle number.